TEKNOLOGI WIRELESS SENSOR NETWORK UNTUK APLIKASI PEMANTAUAN SUHU DAN INTENSITAS CAHAYA PADA PERTANIAN - Palestina , Sari; Effendi, Yasin (Jurnal Ilmiah Sistem Informasi, 2024)
This research aims to develop and implement a Wireless Sensor Network (WSN) system that is capable of monitoring temperature and light intensity in real-time through the SmartLife application. The system consists of sensor nodes equipped with temperature and light intensity sensors, a gateway for collecting data, and a central server for data storage and analysis. Test results show that the developed WSN system has a high level of accuracy with an average deviation of less than 2%, high reliability with a data loss rate of less than 1%, and energy efficiency that allows continuous operation with battery power sources. The collected data is analyzed to understand patterns of changes in temperature and light intensity under various environmental conditions. The implementation of the smartlife application allows users to monitor data in real-time and provides valuable information for various environmental monitoring applications. The conclusion of this research shows that WSN is an effective and efficient solution for monitoring temperature and light intensity in smartlife and environmental monitoring applications.